IMPACTO DA SAZONALIDADE NA INFECÇÃO POR VERMES PULMONARES EM BOVINOS DA AMAZÔNIA BRASILEIRA - ARAÚJO , Rayssa de Queiroz (2025)
Lungworm infections, primarily caused by Dictyocaulus species, impact cattle health and productivity, yet their epidemiology in tropical regions remains poorly understood. This study aimed to evaluate the seasonal dynamics of Dictyocaulus infection in cattle from the Brazilian Amazon and assess environmental influences on prevalence. A longitudinal study was conducted on a beef cattle farm, monitoring two groups of untreated Nelore females: Experiment 1 (16–18 months old) and Experiment 2 (9–10 months old). Fecal samples were analyzed using the modified Baermann technique, multiplex PCR, and next-generation sequencing (NGS). Climatic data were recorded, and statistical analyses included Spearman’s correlation, Fisher’s exact test, and odds ratio (OR) calculations. A strong seasonal effect on Dictyocaulus infection was observed. In Experiment 1, prevalence was initially high in the dry season (28.7%) but declined, while in Experiment 2, it was significantly higher in the rainy season (41.2%) than in the dry season (12.8%), with an OR of 4.78 (95% CI: 2.74–8.63). Molecular identification confirmed the presence of Dictyocaulus sp. however, the detection of additional sequences or the possibility of nonspecific amplification raises questions about the true identity of the species. Dictyocaulus infection in the Amazon is strongly influenced by seasonality, with precipitation and humidity favoring transmission. Younger animals exhibited higher susceptibility, highlighting the role of immune development. These findings emphasize the need for tailored parasite control strategies in tropical regions. Further research utilizing species-specific molecular tools is essential to refine taxonomic identification and improve management practices.